(untitled) (Research, Society and Development, 2024)
Objective: This article aims to document the planning and methodological conduct of a scoping review, which aims to map the available evidence on using deep abdominal and trunk exercises - known as stabilization exercises - associated with Core Muscle Training. Pelvic Floor (PFMT) in the treatment of urinary incontinence (UI) in adult women. Methodology: the development of the protocol was carried out based on the guidelines of the Joanna Briggs Institute (JBI) and Preferred Reporting Items for Systematic Review- Extension for Scoping Review (PRISMA -ScR). A search strategy will be used in seven databases and two gray literature repositories, without language or year restrictions. All study designs and sources of evidence involving women in any context and with any subtype of UI will be eligible for inclusion. Studies that associate exercise with medication or surgery will be excluded. The included articles will be imported into the Rayyan® reference management software to be independently selected by reviewers, following the three steps proposed by the JBI guidelines. The extracted data will be presented in tables and a narrative summary, with the process presented in a flowchart. Final considerations: the results are expected to reveal how research on the treatment of UI in adult women using trunk stabilization exercises associated with PFMT has been conducted, as well as knowledge gaps, protocol characteristics, and outcomes. The protocol was registered with the Open Science Framework to provide greater transparency to the process.